Effectiveness of Using Artificial Intelligence in Emergency Medical Diagnosis - Ayman Mohammed Alzahrani; Ibrahim Hilal Al Zahrani; Ammar Abdul Aziz Al-Naqeb; Khaled Ali Asiri; Mohammed Khaled Al-Subhi; Essam Abdullah Al-Shaibi; Mohammed Saleh Alsulimi; Emad Saleh Alsulimi; Ahmed Abdulrahman Alzahrani (International Journal of Medical Toxicology and Legal Medicine, 2024)
The use of Artificial Intelligence (AI) in emergency medical diagnosis is increasingly recognized as a tool to enhance the speed, accuracy, and overall effectiveness of healthcare delivery in critical situations. AI technologies, including machine learning algorithms, natural language processing, and computer vision, offer the potential to support healthcare professionals by analyzing vast amounts of data in real-time, improving diagnostic precision, and optimizing patient triage. This paper examines the effectiveness of AI in emergency medical settings, highlighting its role in improving diagnostic accuracy, accelerating decision-making processes, and mitigating cognitive biases in high-pressure environments. Additionally, it explores the integration of AI into clinical workflows, addresses the ethical and legal challenges associated with AI adoption, and evaluates its potential to reduce diagnostic errors. While AI's implementation in emergency medical diagnostics presents some challenges, such as data privacy and the need for system validation, its ability to transform emergency healthcare delivery is undeniable. Future advancements in AI could lead to improved patient outcomes and more efficient emergency medical care.